Air cooling techniques and corresponding impacts on combined cycle power plant (CCPP) performance: A review [Techniques de refroidissement de l'air et impacts correspondants sur les performances des centrales lectriques cycle combin] - Deng C.; Al-Sammarraie A.T.; Ibrahim T.K.; Kosari E.; Basrawi F.; Ismail F.B.; Abdalla A.N. (Elsevier Ltd, 2023)
Combined cycle power plants; Electric power generation; Electric power plants; Energy utilization; Environmental impact; Environmental technology; Evaporation; Evaporative cooling systems; Gas compressors; Thermoelectric equipment; Absorption chillers; Evaporative coolers; Evaporative cooling; Inlet air-cooling systems; Inlet-air cooling; Mass flow rate of air; Mechanical chillers; State-of-the art reviews; Cooling